Contribution To The Construction Of The Subject Of Theological Anthropology - Kuc, Leszek (Studia Theologica Varsaviensia, 2020)
"e anthropological upheaval in theology is connected with certain changes in the way of practising philosophy in the (/ and ) centuries. Of course, Kant’s revolution was of fundamental importance. With regard to the theological anthropology of K. Rahner’s situation, it can be described as follows: “…this is a critical reflection, which does not pass to the agenda over Kant’s ‘Copernican revolution,’ but draws attention to the creative role of the subject in the process of cognition. A phenomenological reflection leN its mark on Rahner, from which he took over the conviction that we perceive existence only through consciousness, more precisely: we learn about the structures of existence through the analysis of the given consciousness. So here is the source of the transcendental character of Rahnerian anthropology. It is simply a reflection on man at the level of a priori conditions, anticipating external experience. "is is not necessarily a chronological order, but certainly a logical one, since every philosophical question about the external existence contains a hidden question about the sense of human existence.”